Characteristics of adolescent pregnancy, Brazil - Simões, Vanda Maria Ferreira; Silva, Antônio Augusto Moura da; Bettiol, Heloisa; Lamy-Filho, Fernando; Tonial, Sueli Rosina; Mochel, Elba Gomide (Revista de Saúde Pública, 2003)
OBJECTIVE: To identify the main socioeconomic, demographic, anthropometric and behavioral characteristics, and pregnancy outcomes of adolescent pregnancy and to assess health services used by pregnant adolescents. METHODS: Data were collected from a cross-section of 2,429 deliveries by women residing in the municipality of São Luís, Brazil, of which 94% were hospital births. Women were categorized into six age groups. The two groups of teenagers (under 18 and 18-19 years) were compared to four groups of older women. Comparison was also made between the two teenage groups. The chi-square test was used to compare proportions and prevalence ratio was used as an effect measure. RESULTS: Of 2,429 women, 714 (29.4%) were adolescents. Their specific fertility coefficient was higher than in other regions of the country. Adolescents showed lower socioeconomic and reproductive conditions than older women and a higher proportion of inadequate prenatal care. The majority had no partner. They had the lowest percentages of caesarean section and smokers. CONCLUSIONS: Despite their equally unfavorable socioeconomic situation, 18-19 year-old adolescents had pregnancy outcomes comparable to the age group 25-29, whereas those under 18 had the highest proportions of low birth weight, preterm birth, and infant mortality rate. This suggests that biologic immaturity may be associated with adverse pregnancy outcomes.